2002
DOI: 10.1037/0090-5550.47.2.230
|View full text |Cite
|
Sign up to set email alerts
|

Suggestions for psychologists working with Mexican American individuals and families in health care settings.

Abstract: The number of Mexican Americans in the United States continues to grow at a rapid rate. As these numbers increase, so does the likelihood that Mexican Americans will eventually come into direct contact with the health care system. Mexican Americans with traditional Mexican attitudes, values, and behaviors encounter barriers as they attempt to access medical and rehabilitative care. Issues such as acculturation, language, family, interdependence, attitudes toward authority, and time orientation are some of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 3 publications
0
12
0
Order By: Relevance
“…Culturally competent services for health care providers based on the findings related to simpatía include: mirroring empathy demonstrated by Latino families, frequently encouraging families to ask questions, normalizing their voicing areas of concern regarding their child’s medical treatment, and providing additional time for families to become more confident in directly expressing apprehension or disagreement (e.g., Andrés-Hymen, et al, 2006). In addition, rather than assuming that a family that has not requested an interpreter does not in fact need one or relying on family members to interpret, it is the responsibility of the medical team to ensure that information and services are provided in Spanish through use of trained interpreters or bilingual professionals (Sharma & Kerl, 2002). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Culturally competent services for health care providers based on the findings related to simpatía include: mirroring empathy demonstrated by Latino families, frequently encouraging families to ask questions, normalizing their voicing areas of concern regarding their child’s medical treatment, and providing additional time for families to become more confident in directly expressing apprehension or disagreement (e.g., Andrés-Hymen, et al, 2006). In addition, rather than assuming that a family that has not requested an interpreter does not in fact need one or relying on family members to interpret, it is the responsibility of the medical team to ensure that information and services are provided in Spanish through use of trained interpreters or bilingual professionals (Sharma & Kerl, 2002). …”
Section: Discussionmentioning
confidence: 99%
“…Sharma and Kerl (2002) also discuss the importance of attending to the degree of deference accorded to authority figures and differences in time orientation when working with Latino families. Culture can also influence perceptions of health care providers and thus overall effectiveness of medical treatment.…”
Section: Introductionmentioning
confidence: 98%
“…18,19 Common system level barriers are financial difficulties and lack of health insurance; inaccessible health care facilities, time conflicts, and long waits; lack of transportation and lack of child care; and lack of bilingual staff that is representative of the Hispanic community. [20][21][22][23] Two recent studies found racial/ethnic disparity in receiving treatment for an eating disorder. Among those who had sought care, proportionately fewer minority women actually received treatment than was true for White women.…”
Section: Methodmentioning
confidence: 99%
“…In recent decades emphasis has been placed on increasing cultural awareness and sensitivity within therapeutic and medical settings (Bean, Perry & Bedell, 2001;Hardy & Laszloffy, 1995;Plummer, 1995;Sharma & Kerl, 2002) when working with clients from varied cultural and ethnic backgrounds. Cultural sensitivity trainings for practitioners such as Hardy and Laszloffy's (1995) cultural genogram activity, among others, have been developed and utilized in this process.…”
Section: Chapter One Introductionmentioning
confidence: 99%
“…Articles have been published which suggest how to best work with ethnically and culturally diverse clients (Sharma & Kerl, 2002) based on the researcher's/practitioner's understanding of values and norms of the clients' culture of origin. Although these have all been good faith attempts to provide the best possible services to culturally and ethnically diverse clients, these efforts have also been overwhelmingly ethnocentric as the majority of these studies have been published from the perspective of how these 'other' cultures and people differ from the dominant White American culture and its people (Fontes, 2005), and therefore how to best work with them despite these differences.…”
Section: Chapter One Introductionmentioning
confidence: 99%